Evaluation of the condition for storing pollen grains of japanese melon \(Cucumis melo\) L. (Cucurbitaceae) - Dong Phuong, Nguyen Tran; Sang, Mai The (Academia Journal of Biology, 2021)
In recent years, studies have been carried on the selection and breeding of melon to reduce its production cost. The F1 seeds of this species are usually created by parental lines. Notably, the parental lines are separated from each other to secure the breeding materials. However, there are no studies on establishing suitable conditions for storing pollen grains of Japanese melon Cucumis melo L. In this study, pollen grains of C. melo were dried at 38 oC temperature, for 1.5 hours, which served as the raw materials. After storage in acetone at 5 oC for 3, 5, 7 days, or in liquid nitrogen for 5 days, pollen grains were stained with triphenyl tetrazolium chloride (TTC) to evaluate their viability and pollination ability. Then, the following parameters including pollen grains’ survival rate, morphology analysis of pollen grains, pollen grains’ fruiting rate, fruit weight, firm seed rate, and germination of melon seeds were analyzed. The study results show that the grains’ survival rates were 86.58%, 88.38%, 87.28% or 88.58% in the group stored in acetone for 3, 5, 7 days or liquid nitrogen for 5 days, respectively. The fertilized fruit rate was 100% in the group stored in liquid nitrogen for 5 days. But the rate of germination from firm seeds was highest, with 94.00% in the group stored in acetone for 3 days. The best method is storing the pollen grains in acetone for 3 days.